4 Pillars for Effective Physics Learning in The Times of Corona - Muslimin Muslimin; Rahmi Dewi; Darmawan Darmawan (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2020)
Changing the learning process from face-to-face to online learning during the outbreak of COVID-19 raises many problems such as ineffective learning, experiments that can't be done in the laboratory, and the 4 pillars of Education are ignored. The purpose of this research is to get information how 4 pillars as a solution for the existing problems. The results of this study are project-based learning can be used as a solution for ineffective learning, and Virtual Laboratory for experiments that cannot be done in the laboratory. Therefore during the covid-19 pandemic, the Four Pillars of Education can be applied by maximizing project-based learning and virtual laboratory using 3 learning spaces like Virtual synchronous learning, self-directed asynchronous learning, and Collaborative Asynchronous learning